Effect of Qualitative Feed Restriction in Broiler Breeder Pullets on Stress and Clinical Welfare Indicators - Tahamtani, Fernanda M.; Moradi, Hengameh; Riber, Anja B. (Frontiers in Veterinary Science, 2020)
The feed restriction applied during rearing of broiler breeders inflicts chronic hunger and frustration due to unfulfilled behavioural needs for feeding. To alleviate the welfare problems associated with feed restriction, qualitative feed restriction allows a larger amount of feed to be provided without increasing the energy intake. In the present study, the aim was to investigate the effect of scatter-fed qualitative feed restriction on a range of welfare indicators in broiler breeders at the end of the rearing period. In total, 1200 female breeder chicks of the genotype Ross 308 were housed in 24 pens: six pens of initially 50 birds per dietary treatment. The treatments were: 1) standard feed (Control), 2) standard feed diluted with oat hulls (Insoluble), 3) standard feed diluted with oat hulls and sugar beet pulp (Mixed) and 4) standard feed plus maize silage (Roughage). At 15 weeks of age, a blood sample was taken from 40 birds (10/treatment) five times within 24 h. The plasma was analysed for corticosterone concentration. At 19 weeks of age, a clinical welfare assessment was performed on all birds before they were sacrificed. From each bird, three feathers were plucked and macroscopically examined for the presence of fault bars. Feather length and weight were also recorded. Mortality was registered on occurrence throughout the rearing period. Treatment affected the plumage condition, footpad dermatitis, plumage dirtiness, vent pasting, and number of severe fault bars (P ≤ 0.05) but not plasma corticosterone concentration, hock burns, hyperkeratosis and mortality (P ≥ 0.17). There was an effect of the interactions between treatment and feather type on the total number of fault bars per feather, average position of the fault bars relative to the base of the feather, and growth rates of feather mass and length (P < 0.0001). Overall, the results showed improved welfare of Roughage birds and reduced welfare of Mixed birds, whereas the welfare of Insoluble birds did not seem to differ noticeably from that of Control birds. We recommend to further develop a feeding strategy that includes daily allocation of roughage to broiler breeders during the rearing period.